An Expanding Shadow in the Brain: A Case Series with a Review of Literature on Primary CNS Lymphoma - Pal, Debasmita; Kumar, Adesh; Shetty, Vijith; L., Kishan Prasad H.; Rao, Malikarjuna (Indian Journal of Medical and Paediatric Oncology, 2025)
Primary central nervous system lymphoma (PCNSL) is a rare, aggressive subtype of non-Hodgkin lymphoma that arises within the central nervous system, often affecting immunocompromised individuals, particularly those with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). Diagnostic and therapeutic challenges stem from its diverse clinical presentations, deep parenchymal involvement, and the protective effect of the blood–brain barrier, which limits chemotherapeutic penetration. While most cases are diffuse large B cell lymphomas, rare T cell variants highlight the critical role of tissue biopsy and immunohistochemistry in confirming diagnosis.We present five patients diagnosed with PCNSL who exhibited varied neurological symptoms, including headache, vomiting, behavioral changes, and focal deficits. Diagnostic workup included magnetic resonance imaging, positron emission tomography/computed tomography, cerebrospinal fluid (CSF) analysis, and stereotactic or open brain biopsy. Treatment was tailored based on immune status: immunocompetent patients received rituximab, methotrexate, procarbazine, and vincristine, while immunocompromised patients were treated with methotrexate, temozolomide, and rituximab. Radiotherapy was used selectively. One case involved surgical excision for a suspected meningioma, later confirmed as a rare T cell variant.Outcomes ranged from long-term remission to early mortality, particularly in HIV-positive patients with profound immunosuppression. This series emphasizes the importance of early treatment initiation, tailored therapy, and the consideration of rare pathological variants. Novel biomarkers, such as myeloid differentiation primary response 88 mutations and CSF cytokines such as interleukin-10 and chemokine CXCL13, show potential for improving diagnosis and prognosis but require further validation.
Keywords: case series; primary CNS lymphoma; biomarkers; T cell; imaging